Grape exosome-like nanoparticles: A potential therapeutic strategy for vascular calcification - Teng, Yintong; He, Jiaqi; Zhong, Qingping; Zhang, Yangmei; Lu, Zhenxing; Guan, Tianwang; Pan, Yuxuan; Luo, Xiaodi; Feng, Weijing; Ou, Caiwen (Frontiers in Pharmacology, 2022)
Vascular calcification (VC) is prevalent in hypertension, diabetes mellitus, chronic kidney disease, and aging, and has been identified as an important predictor of adverse cardiovascular events. With the complicated mechanisms involved in VC, there is no effective therapy. Thus, a strategy for attenuating the development of VC is of clinical importance. Recent studies suggest that grape exosome-like nanoparticles (GENs) are involved in cell–cell communication as a means of regulating oxidative stress, inflammation, and apoptosis, which are known to modulate VC development. In this review, we discuss the roles of GENs and their potential mechanisms in the development of VC.